1988
DOI: 10.1677/jme.0.0010179
|View full text |Cite
|
Sign up to set email alerts
|

Actions of pertussis toxin on the inhibitory effects of dopamine and somatostatin on prolactin and growth hormone release from ovine anterior pituitary cells

Abstract: Forskolin and the phorbol ester 12-O-tetradecanoylphorbol 13-acetate stimulate prolactin and GH release from ovine anterior pituitary cells cultured in vitro. Dopamine and somatostatin inhibit release of prolactin and GH respectively, after stimulation by these agents, but without effects on intracellular cyclic AMP concentrations. In each case the inhibitory effects were reversed by pretreatment of cells with pertussis toxin, in a dose-related fashion (1-100 ng/ml), again without affecting cyclic AMP levels. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
5
0

Year Published

1989
1989
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 36 publications
2
5
0
Order By: Relevance
“…TPA pretreatment had no significant effect on basal CAMP levels, but led to significantly enhanced stimulation of CAMP concentration by GHRH (table 1). Somatostatin had no effect on CAMP levels, irrespective of TPA pretreatment, in accordance with previous results in ovine pituitary cells [12,13].…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…TPA pretreatment had no significant effect on basal CAMP levels, but led to significantly enhanced stimulation of CAMP concentration by GHRH (table 1). Somatostatin had no effect on CAMP levels, irrespective of TPA pretreatment, in accordance with previous results in ovine pituitary cells [12,13].…”
Section: Resultssupporting
confidence: 92%
“…TPA (100 ng/ml) stimulated secretion of GH and prolactin from ovine anterior pituitary cells as shown previously [5,12]. Pretreatment of the cells with 0.1-1000 ng/ml TPA for 5 h resulted in a dose-dependent inhibition of this stimulatory effect ( fig.1).…”
Section: Resultssupporting
confidence: 85%
“…Early studies suggested that inhibition of cAMP production contributes to inhibition of PRL release (578,580). However, the relevance of cAMP in dopamine actions on PRL release was questioned by the finding that dopamine inhibits PRL secretion in cells with activated ACs by forskolin (582). We also observed that the dopamine agonist-induced inhibition of basal release of prestored PRL was preserved when cAMP levels were elevated by forskolin treatment (583).…”
Section: Dopamine Modulation Of Calcium Influx In Lactotrophs and Melmentioning
confidence: 73%
“…Such an action could be coupled to the effects of cAMP and its kinase on the exocytotic pathway (23) and/or inhibition of Ca 2ϩ signaling pathway (24). However, the relevance of cAMP in dopamine actions on PRL release was questioned by the finding that dopamine inhibits PRL secretion in cells with activated ACs by forskolin (25).…”
mentioning
confidence: 99%